Nanomaterials : Basic Concepts and Applications - Virk, Hardev Singh, 1942- (Diffusion and defect data. Solid state phenomena, 2015)
The present volume "Nanomaterials: Basic Concepts and Applications", as the title suggests, deals with basic concepts and applications of anomaterials, a buzz word in the modern world of Science and Technology. Because of advanced characterization and new fabrication techniques, nanomaterials are now central to multiple disciplines, including materials science, chemistry, physics, engineering and medicine. This special volume under Solid State Phenomena series will present an overview of recent research developments, including synthesis, characterization, and applications, in Nanoelectronics.